Malignant Ascites - Chandran, Rabindran; Gedam, D Sharad (International Journal of Medical Research and Review, 2016)
Ascitis is common entity in adults. Increased vascular permeability, decerse plasma oncotic pressure & lymphatic obstructions are common causes.